Efek Aplikasi Synechococcus sp. pada Daun dan Pupuk NPK terhadap Parameter Agronomis Kedelai - R. Soedradjad; Sholeh Avivi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Synechococcus sp. is a species photosynthetic bacterium that has symbiotic mutualism with plant.  Research on this field is not many. Foliar application of this bacterium may increase the growth and yield characteristics.  The aim of this research was to determine the effect of Synechococcus sp. application and NPK fertilizer on soybean growth and yield.  The research was conducted in Pusat Inkubator Agribisnis (PIA) Jember University on February until May 2004.  Split plot design was used with 2 factors, Synechococcus sp. as sub plot (B0: without bacteria and B1: with bacteria application) and NPK fertilizers as main plot (P0: 0 g/plant; P1: 0.347 g/plant; and P2: 0.875 g/plant) with three replications. The result showed that the interaction between Synechococcus sp. and NPK fertilizers treatments was not significant.  The  bacteria applications significantly increasing plants growth (42.9%), leaf area index (294.6%), number of productive stem per plant (141.3%), number of productive nodes per plant (40.3%), pods weight per plant (175.2%), number of pods per plant (152.8%), grain weight per plant (80.5%), dry weight (209.8%), and 100 grains weight per plant (3.4%).  The fertilizers significantly affected only on plants growth (44.6%) and number of pods per plant (29.4 %).    Key words:  Glycine, Synechococcus sp., NPK